Diplomatic Rhetoric Analysis: Indonesia's Palestine Advocacy at International Court of Justice - Rosadi, Raesita Rakhmawati (UPT Publikasi Ilmiah UNISBA, 2025)
Indonesia has consistently supported Palestine through public diplomacy efforts, but studies on the rhetorical strategies used in this advocacy remain limited. This study aims to analyze the speech delivered by Indonesian Foreign Minister Retno Marsudi at the International Court of Justice on February 23, 2024, as the primary object of research. The speech available at https://youtu.be/aozx9-fBt-k?feature=shared, serves as the textual corpus for identifying rhetorical strategies used to influence global opinion and policy. Using Aristotle's Five Canons of Rhetoric (discovery, arrangement, style, delivery, and memory), this research examines the integration of legal arguments, moral authority, and emotional appeal in diplomatic discourse. The findings show that Marsudi leveraged Indonesia's anti-colonial heritage and historical ties with Palestine to deliver a speech that blended legal logic, ethical principles, and emotional resonance. This rhetorical strategy strengthened Indonesia's position in the Israel–Palestine conflict while affirming its global role in advocating for justice. The speech demonstrates how historical context, and moral narratives can influence international policy. Practically, this research highlights the importance of integrating historical narratives and ethics into diplomacy. Theoretically, this study contributes to the development of rhetorical studies in international political communication and the analysis of multilateral diplomatic discourse.